DLL3 as an Emerging Target for the Treatment of Neuroendocrine Neoplasms - Yao, James; Bergsland, Emily; Aggarwal, Rahul; Aparicio, Ana; Beltran, Himisha; Crabtree, Judy S.; Hann, Christine L.; Ibrahim, Toni; Byers, Lauren A.; Sasano, Hironobu; Umejiego, John; Pavel, Marianne Ellen (Oncologist, 2022)
This review describes neuroendocrine neoplasms (NEN) classification, incidence, pathogenesis, and current management, focusing on delta-like ligand 3 (DLL3) in NEN progression and prognosis. Therapeutic targeting of DLL3 is addressed, and ongoing studies of DLL3-targeting therapies are summarized.
CRIS-Team WoS Importer:2022-08-26